Professional work : knowledge, power and social inequalities - Gorman, Elizabeth M.; Vallas, Steven P. (Steven Peter), 1951- (Bingley, U.K. : Emerald Publishing Limited, 2020)
The professions have undergone massive changes in recent decades, as globalization, information technology, bureaucratization and market competition have begun to envelop even the most prestigious occupations in contemporary societies. Ironically, at a time when expert knowledge has grown increasingly important, the 'golden age' of the professions has receded into the past. Professional autonomy, authority, and ethics are all under siege, and even their claims to exclusive control of knowledge face challenges on multiple fronts. Volume 34 of Research in the Sociology of Work explores how the professions are faring in this changed world, shedding new light on a field that has long been at the center of social science thinking about the economy, the state, and social order. Chapters in this volume explore a series of questions that are vital to modern life, such as: How has increased control by employers and clients altered the experience of work for professionals? What are the new bases of professional status? How are underrepresented groups faring within the professions? How do professionals respond to precarity and unemployment?
Chapter 1: Introduction; Elizabeth Gorman and Steven Vallas -- Thematic Papers -- Chapter 2: Professional engagement in articulation work: implications for experiences of clinical and workplace autonomy; Jane S. VanHeuvelen -- Chapter 3: The intimate dance of networking: a comparative study of the emotional labors of young American and Danish jobseekers; Sabina Pultz and Ofer Sharone -- Chapter 4: Teaching on contract: job satisfaction among non-tenure-track faculty; Elizabeth Klainot-Hess -- Chapter 5: Education and referrals: parallel mechanisms of white and asian hiring advantage in a Silicon Valley high technology firm; Koji Chavez -- Chapter 6: Skill development practices and racial-ethnic diversity in elite professional firms; Elizabeth H. Gorman and Fiona M. Kay -- Chapter 7: Professional impurities; Sida Liu -- Chapter 8: Measured success: knowledge, power, and inequality in the professional work of evaluation; Elisa Martínez, Laurel Smith-Doerr, Timothy Sacco Papers at Large -- Chapter 9: Labor, lifestyle, and the "ladies who lunch": work and worth among elite stay at home mothers; Jussara do Santos Raxlen and Rachel Sherman -- Chapter 10: Manufacturing discontent: the labor process, job insecurity and the making of "good" and "bad" workers; Martha Crowley, Julianne Payne, and Earl Kennedy.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Professions -- Sociological aspects; Business & Economics, Workplace Culture; Organizational theory & behaviour